Long-Term Running Exercise Delays Age-Related Changes in White Matter in Rats - Chen, Lin; Chao, Feng-lei; Lu, Wei; Zhang, Lei; Huang, Chun-xia; Yang, Shu; Qiu, Xuan; Yang, Hao; Zhao, Yuan-yu; Wang, San-rong; Li, Chen; Tang, Yong (Frontiers in Aging Neuroscience, 2020)
Running exercise, one of the strategies to protect brain function, has positive effects on neurons and synapses in the cortex and hippocampus. However, white matter, as an important structure of the brain, is often overlooked, and the effects of long-term running exercise on white matter are unknown. Here, fourteen-month-old male Sprague-Dawley (SD) rats were divided into a middle-aged control group (18-month-old control group), an old control group (28-month-old control group) and a long-term runner group (28-month-old runner group). The rats in the runner group underwent a fourteen-month running exercise regime. Spatial learning ability was tested using the Morris water maze, and white matter volume, myelinated fiber parameters, total mature oligodendrocyte number and white matter capillary parameters were investigated using stereological methods. The levels of growth factors related to nerve growth and vascular growth in peripheral blood and the level of Neurite outgrowth inhibitor-A (Nogo-A) in white matter were measured using an enzyme-linked immunosorbent assay (ELISA). The present results indicated that long-term running exercise effectively delayed the age-related decline in spatial learning ability and the atrophy of white matter by protecting against age-related changes in myelinated fibers and oligodendrocytes in the white matter. Moreover, long-term running exercise prevented age-related changes in capillaries within white matter, which might be related to the protective effects of long-term exercise on aged white matter.